Analisis strategi pemasaran produk cicil emas dalam meningkatkan minat nasabah pada Bank Syariah Indonesia Kota Pekanbaru - Erman, Nilam; Winario, Mohd. (STAI Auliaurrasyidin Tembilahan, 2025)
Cicil Emas is an Islamic investment product that facilitates gold ownership through an installment system based on the murabahah contract. This study aims to analyze the marketing strategy of Bank Syariah Indonesia (BSI) for the Cicil Emas product and to examine its influence on customer interest in Pekanbaru City. A descriptive qualitative method was employed, with data collected through in-depth interviews, observation, and document analysis involving informants from the bank's internal divisions (marketing and financing) as well as customer users and non-users of the product. The findings indicate that BSI's marketing strategy encompasses digital education, social media promotion, community-based outreach, and collaboration with religious figures. Factors influencing customer interest include the perceived value of gold investment, payment flexibility, transparency of the sharia contract, and social influence. This strategy is assessed as moderately effective in enhancing customer understanding and interest, despite obstacles such as the low level of Islamic financial literacy among some community segments. In conclusion, BSI's marketing strategy aligns with sharia principles and contributes to building public trust in the Cicil Emas product.